Refractory hypothyroidism - Lai, Yin Ye; Thambiah, Subashini Chellappah; Mohamed Mokhtar, Normaizuwana; Samsudin, Intan Nureslyna (Malaysian Society of Pathologists, 2024)
Introduction: Persistently elevated thyroid stimulating hormone (TSH) despite levothyroxine (LT4) treatment that exceeds the standard weight-adjusted dose is a common clinical presentation. This may lead to additional testing for LT4 malabsorption or poor LT4 adherence, the latter of which is challenging to confirm because it is predicated on accurate patient accountability. Case report: A 35-year-old lady, post-radioactive iodine therapy for Graves’ disease remained euthyroid for a year on oral LT4. Two years later, she was clinically and biochemically hypothyroid despite claiming LT4 compliance. As all laboratory investigations were within the reference range, pseudomalabsorption was suspected and a LT4 absorption test was done. During the test, her free thyroxine increased significantly at 4 hours, reaching a peak of more than 50 from baseline while TSH decreased appropriately from 0 minute to 360 minutes. This was followed by normalisation of TSH with LT4 treatment under direct observation. Discussion: The LT4 absorption test is a prompt and economical means to rule out true malabsorption, decrease unwarranted subspecialty referrals and validate the weight-adjusted LT4 dose reduction.